Knowledge in Wonderland: A Media Ecology Perspective of the Epistemological Influence of the Wonderland of Knowledge – A Children’s Encyclopaedia From the Early 1940s - Mules, Pip (Ingenta, 2016)
This article is a media ecology perspective of the epistemological influence of The Wonderland of Knowledge – a children’s encyclopaedia from the early 1940s. It has shown how the highly mechanized production and distribution processes and the highly sedimented material form of this medium mediated perceptions such as: that knowing is an objective, emotionally detached experience; that knowledge is unchanging; that it is possible to know about the world as a certain, unambiguous, decontextualized story and that there is a body of correct knowledge that could be absorbed and considered to be appropriate for everyone. This analysis has also revealed a number of contradictions between the highly sedimented material form of the medium and the more oral elements of its content. In particular, elements of the content are ‘close to the human life world’, homeostatic and aggregative rather than subordinative.
Keywords: Wonderland of Knowledge; Children's encyclopaedia; Encyclopaedic knowledge; Epistemological beliefs; Epistemology; Illustrated encyclopaedia; Orality